Observation of Cherenkov diffraction radiation from 3D printed plastic targets; Journal of Instrumentation; Vol. 20, iss. 7 - Bushmina E. A. Elizaveta Alekseevna; Alekseev S. V.; Baldin A. A. Anton Aleksandrovich; Bleko V. V. Vitold Vladislavovich; Bulavskaya A. A. Angelina Aleksandrovna; Karataev P. V. Pavel Vladimirovich; Kidanova E. A. Ekaterina Alekseevna; Kishin I. A.; Klenin A. A.; Kocharian (Kocharyan) V. R. Vagan Rashidovich; Kubankin A. S. Aleksandr Sergeevich; Margaryan V. Vardan; et al. (2025, 2025)
Title screen